Efektivitas Curcuma Longa sebagai Herbal Preventif dalam Bidang Obstetri-Ginekologi, Pediatri, dan Patologi Anatomi : Kajian Sistematik - Fransiska Mochtar; Saddam Muhdi; Hengky Ardian; Siska Silviana (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Curcuma longa (turmeric) is a widely known herbal plant due to its active compound, curcumin, which possesses anti-inflammatory, antioxidant, and immunomodulatory properties. This review aims to evaluate the preventive effectiveness of Curcuma longa in the fields of obstetrics-gynecology (obgyn), pediatrics, and anatomical pathology. The review was conducted following the PRISMA 2020 guidelines. Literature was searched from PubMed, Scopus, Cochrane Library, and Google Scholar for studies published between 2015 and 2025. Keywords used included: